METHODS FOR DESCRIPTION, ANALYSIS AND EVALUATION OF COMMAND AND CONTROL SYSTEMS (C2) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Every organization needs a clear understanding of its own processes, capabilities, products, technologies and relationships to effectively deliver its objectives in response to a changing environment. A clear understanding of the nature of management systems requires an integrated abstract representation of their multifaceted aspects through organisational modelling methods. When the system is complex, an approach that can provide a unified medium for representing all major functional and system perspectives is necessary for its comprehensive modelling.  The purpose of this publication is to present an approach that provides an integration into one environment of organizational goals; policies, concepts, and doctrines; management systems; decision-making procedures; organizational structures, processes, information flows, and data; resources, capabilities, and technologies. In this approach, architecture refers to the fundamental organization of a system, which includes the system components, their relationships with each other and with the environment, and the principles that underlie system design and its development.